Cannabinoid type 1 receptors transiently silence glutamatergic nerve terminals of cultured cerebellar granule cells. - Jorge Ramírez-Franco; David Bartolomé-Martín; Beatris Alonso; Magdalena Torres; José Sánchez-Prieto (PLoS ONE, 2014)
Cannabinoid receptors are the most abundant G protein-coupled receptors in the brain and they mediate retrograde short-term inhibition of neurotransmitter release, as well as long-term depression of synaptic transmission at many excitatory synapses. The induction of presynaptically silent synapses is a means of modulating synaptic strength, which is important for synaptic plasticity. Persistent activation of cannabinoid type 1 receptors (CB1Rs) mutes GABAergic terminals, although it is unclear if CB1Rs can also induce silencing at glutamatergic synapses. Cerebellar granule cells were transfected with VGLUT1-pHluorin to visualise the exo-endocytotic cycle. We found that prolonged stimulation (10 min) of cannabinoid receptors with the agonist HU-210 induces the silencing of previously active synapses. However, the presynaptic silencing induced by HU-210 is transient as it reverses after 20 min. cAMP with forskolin prevented CB1R-induced synaptic silencing, via activation of the Exchange Protein directly Activated by cAMP (Epac). Furthermore, Epac activation accelerated awakening of already silent boutons. Electron microscopy revealed that silencing was associated with synaptic vesicle (SV) redistribution within the nerve terminal, which diminished the number of vesicles close to the active zone of the plasma membrane. Finally, by combining functional and immunocytochemical approaches, we observed a strong correlation between the release capacity of the nerve terminals and RIM1α protein content, but not that of Munc13-1 protein. These results suggest that prolonged stimulation of cannabinoid receptors can transiently silence glutamatergic nerve terminals.